Lignin p-Hydroxybenzoylation Is Negatively Correlated With Syringyl Units in Poplar - Mottiar, Yaseen; Mansfield, Shawn D. (Frontiers in Plant Science, 2022)
The lignin found in the cell walls of poplar fibres is decorated with ester-linked p-hydroxybenzoate moieties that originate from the participation of acylated monolignols in lignin polymerisation. Although little is known about the biological implications of these cell-wall constituents, it has historically been postulated that acylated monolignols might promote lignification in syringyl lignin-rich species such as poplar. However, cell-wall-bound p-hydroxybenzoate groups were negatively correlated with syringyl units in a collection of 316 unrelated genotypes of black cottonwood (Populus trichocarpa). Based upon this observation, several alternative hypotheses on the occurrence of lignin acylation are presented.